2022
DOI: 10.2298/tsci200926168d
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on flow and heat transfer performance of serpentine parallel flow channels in a high voltage heater system

Abstract: In this study, a high-voltage heater system with a size of 310 mm ? 210 mm ? 60 mm has been numerically studied and experimentally verified to explore the influence of the cavity structure on the flow and heat transfer performance. the response surface model and analysis of variance are used to determine the influence of the length of the mainstream area of the inlet (Lin), the length of the mainstream area of the outlet (Lout), the length of the parallel flow channel (Lch) and the single cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous research on the commercialization of HVLH [7,8] along with computer-aided engineering (CAE) investigations on the performance and design of products [9][10][11][12] have focused mainly on the advancement of the heater system itself. On the other hand, block diagram modeling approaches have been used to develop and implement HVLH control strategies at the system level, particularly when incorporated into EV or PHEV HVAC modules [13][14][15][16].…”
Section: Transfer Function Modeling and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research on the commercialization of HVLH [7,8] along with computer-aided engineering (CAE) investigations on the performance and design of products [9][10][11][12] have focused mainly on the advancement of the heater system itself. On the other hand, block diagram modeling approaches have been used to develop and implement HVLH control strategies at the system level, particularly when incorporated into EV or PHEV HVAC modules [13][14][15][16].…”
Section: Transfer Function Modeling and Discussionmentioning
confidence: 99%
“…The discretization of the computational domains resulted in a total of 32,010,895 3D elements, with 24,856,397 elements in the fluid domain and 7,154,498 in the solid domain, along with 24,704 layered shell elements designated for thin films. Earlier research has shown that around 2.5 million elements are required to achieve precise and convergent results in CFD and CHT studies of comparable heaters [9][10][11][12]. Consequently, the number of elements used in this study is considered adequate for reliable results.…”
Section: Simulation Setupmentioning
confidence: 99%
See 2 more Smart Citations